Fiber Optic Splicing Training with Mechanical Splicers and Fusion Splicers for Computer and Network Engineering Vocational School Students - Fauzi, Ahmad; Suranegara, Galura Muhammad; Setyowati, Endah; Widodo, Suprih (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Curriculum development is one of the challenges in the world of education. In vocational schools with Computer and Network Engineering Skills Competency (TKJ) in particular, these curriculum changes update the Basic Competencies taught. Several changes have been made, including those related to the core competency of fiber optic cable termination. The curriculum renewal means students must improve their core competencies in connecting fiber optic cables. Often, lessons related to fiber optic termination are only given theoretically. This is due to limited support for tools and materials for the fiber optics practicum. This activity will provide a workshop on connecting fiber optic cables to TKJ Skills Competency Vocational School students. As a result, the evaluation of the acceptance of activity materials obtained an average participant score of 88.74% in the very high category. Then, evaluating satisfaction with training activities, it was found that satisfaction with training methods was 94.35% (very high class); training instructors at 93.33% (very high category); and facilities and infrastructure amounting to 95.26% (very high type).